Visum et Repertum: Pemahaman dan Dasar Hukum Penerapannya di Indonesia - prasetyo, yogi (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 14 No 2 (2024): Indonesian Journal of Legal and Forensic SciencesDO - 10.24843/IJLFS.2024.v14.i02.p05, 2025)
This article is the result of research which aims to explain the importance of visum et repertum and the legal basis for its application in Indonesia. The public still does not know or understand the importance of visum et repertum in law. It often happens that legal cases are not resolved properly due to not being supported by a post mortem et repertum. The normative method, which understands law from a legal and regulatory perspective, is used as a way to form a series of research. This research uses data which is the main material from applicable legal regulations and other materials contained in books, journals and written works related to research. The research results show that there is important knowledge about post mortem et repertum which must be understood by the public, so that the public can determine what legal action should be taken if a case is suspected of violating the law. Apart from that, visum et repertum is an important element that cannot be abandoned in the law enforcement process, because its requirements have a legal basis. Various regulations have determined that it is mandatory to have a post mortem et repertum in a case that is suspected of violating the law. Even post mortem et repertum determines the formal and material legal truth.